High-salt intake affects sublingual microcirculation and is linked to body weight change in healthy volunteers: a randomized cross-over trial. Issue 6 (June 2019) - Rorije, Nienke M.G.; Rademaker, Emma; Schrooten, Esmee M.; Wouda, Rosa D.; Homan Van Der Heide, Jacob J.; Van Den Born, Bert-Jan H.; Vogt, Liffert
Abstract : Background: The pathophysiology of salt-sensitive hypertension remains uncertain, but may involve microvascular alterations. High-salt intake decreases microvascular density in hypertensive patients, but due to lack of studies in normotensive patients the causal pathway remains unclear. We studied whether high-salt intake decreases sublingual microvascular density in normotensive individuals and assessed the influence of body weight on changes in microvascular density. Methods: In an open label randomized cross-over trial 18 healthy men were included to study the effect of a 2-week high-salt (>12 g/day) and low-salt (<3 g/day) diet on microvascular (diameter <20 μm) density with sublingual sidestream darkfield imaging. We used sublingual nitroglycerin (NTG) to recruit microvessels. Results: There was no significant difference in microvascular density between diets (0.96 ± 3.88 mm/mm 2 ; P  = 0.31, following NTG; and −0.03 ± 1.64 mm/mm 2 ; P  = 0.95, without NTG). Increased salt intake was correlated with a decrease in microvascular density following NTG ( r  = −0.47; P  = 0.047), but not without NTG ( r  = 0.06; P  = 0.800). The decrease in microvascular density following high-salt intake was significantly larger for those with a large change in body weight as compared with those with a small changer in body weight (−0.79 ± 1.35 and 0.84 ± 1.56 mm/mm 2 respectively, P  = 0.031). Conclusion: We demonstrate in healthy volunteers that higher salt intake is correlated with decreased sublingual microvascular density following administration of NTG and; larger changes in body weight following high-salt intake coincide with a larger decrease in microvascular density. Changes in microvascular density occurred without blood pressure effects, indicating that high-salt load as such contributes to microvascular changes, and may precede hypertension development. Abstract : Supplemental Digital Content is available in the text